PREPARATION AND CHARACTERIZATION OF STARCHâ?TOCOPHEROLS INCLUSION COMPLEXES AS SLOWLY DIGESTIBLE STARCH - Putri Pertiwi Sofyan, Delima
Diabetes is a metabolic disease caused by the body’s inability to control blood sugar. Carbohydrates are the main component of food that is digested into a source of energy and glucose in the body. The control of blood sugar in diabetes patient can be achieved by consuming slowly digestible starch. Slowly digestible starch can be formed drom inclusion complex compound consisting of starch as host molecule and other substances as guest molecules. In this study, the lelected guest molecule is ?-tocopherol because it is hydrophobic and has bioactivity, such as anti-aging, anti-tumor, free radical scavenging, and cardiovascular disease prevention. In this study, the formed inclusion complex is expected to inhibit starch digestion while also having the bioactivity of ?-tocopherol. The research steps include isolation of cassava, complex formation, and enzymatic degradation testing of starch and starch complex. The starch –?-tocopherol complex is formed using conventional heating and microwave methods. The complex was prepared using the conventional method bya dissolving starch (6% w/v aqua dm) in aqua dm for 30 minutes at 90 ?, then adding ?-tocopherol and complexing it for 2 hours. While making the complex using a microwave by dissolving starch (6% w/v aqua dm) in aqua dm for 13 minutes with power 200 W, then adding ?-tocopherol and complexing it for 1 hour.Optimization of starch–?-tocopherol complex by varying the content of ?tocopherol to the starch weight in complex formation (1, 3, 5, 7, 10, 15, and 20%). Starch–?-tocopherol complex tested for empty amylose channels and characterized using UV-VIS solution, FTIR, XRD, and PSA. Enzymatic degradation testing is conducted with various incubation times (3, 15, 30, 60, 120, 180, and 240 minutes). The isolates cassava starch obtained 450,3 g (15% starch) with moisture content 7,6% and an amylose content 15,55% which has same characteristics as conventional starch by spectrum FTIR exhibit peak at 3263 cm-1 , 2918 cm-1, 1635 cm-1 , 1418 cm-1 , 1150 cm-1 and 1000 cm-1 .The inclusion complexe of starch–?tocopherol is successfully formed using both conventional heating and microwave methods. Based on iodine test, ?-tocopherol can reduces the amount of empty amylose channels to 50-20%. The FTIR spectra of the starch–?-tocopherol complex show the same profile as the starch spectra, indicating that ?-tocopherol enter the amylose channels of starch. The X-ray diffractogram of the complex exhibit a peak at 2? = 20°. The formation of the starch –?-tocopherol complex is further confirmed iv by UV spectroscopy, which show new peak at 296 nm. The difference properties between the complex formed by conventional heating and microwave methods is evident from the particle size analyzers result and morphology of complex from SEM. The starch –?-tocopherol complex formed by microwave method has smaller particle size distribution. The result of complex morphological characterization show that starch–?-tocopherol complex using conventional method has lamellar and tube, while the starch–?-tocopherol using the microwave method has lamellar and spherical shape. The starch–?-tocopherol complex formed by both conventional heating and microwave methods can decrease the starch digestion from 12,21%-39,30% and 8,26-35,60%. This indicate that the starch –?-tocopherol complex has been successfully formed using both methods and has the potential to be slowly digestible starch.